Clinical implications of aspirin resistance - Zimmermann, Norbert; Hohlfeld, Thomas (Thrombosis and Haemostasis, 2008)
Aspirin reduces major atherothrombotic events across a wide spectrum of patients with atherosclerotic disease. The occurrence of ischemic events despite of aspirin treatment is a failure of therapy, often denoted ‘clinical aspirin resistance’. This is distinguished from laboratory assays showing an insufficient inhibition of platelet function, which indicate ‘laboratory aspirin resistance’. Laboratory aspirin resistance has been reported in up to 60% of patients after stroke or peripheral arterial disease, up to 70% in stable coronary heart disease and even up to 80% in acute myocardial infarction. However, this data must be interpreted carefully because of small sample sizes and potential confounding factors such as compliance, co-morbidities and large differences between the laboratory methods used for detection. During the past years, evidence has accumulated that laboratory aspirin resistance is associated with an increased incidence of major atherothrombotic events, with an up to 13-fold increased risk of events in patients with cardiovascular disease. Thus, an individualized antiplatelet therapy will have to consider the possibility of aspirin resistance, and the identification of aspirin non-responders may improve antiplatelet therapy in future. Whether an increased dose of aspirin or another antiplatelet drug (e.g. clopidogrel) instead or in addition to aspirin should be given is unclear. Prospective trials are underway which address this issue. This review gives an overview on the various clinical studies that have investigated the prevalence and clinical importance of laboratory aspirin resistance. Moreover, therapeutic options, as well as future perspectives are discussed.
Keywords: Aspirin resistance; atherosclerosis; platelet function; prevalence; clinical outcome